The Shadow Economy in Cyprus: Evidence from the Electricity Consumption and Currency Demand Methods - Andreou, Christoforos K.; Andreou, Elena; Michael, Stephanie; Syrichas, George (My University, 2021)
The recent pandemic has brought about a renewed interest in estimating the size of the shadow economy as governments are striving to find additional revenues to support the fast-declining economic activity and finance their substantial public deficits. This paper provides new estimates of the shadow economy in Cyprus using two different macro approaches; the energy consumption method (ECM) (Kaliberda and Kaufmann, 1996) and the currency demand approach (Tanzi, 1980, 1983). To the best of our knowledge, this is the first paper that applies the energy consumption approach for estimating the shadow economy focusing only on Cyprus. The empirical analysis covers a more recent period, using quarterly data for the period 1995-2018, during which the Cypriot economy has undergone significant structural changes such as financial liberalization, the abolition of capital controls, accession to the European Union, the adoption of the Euro as well as the recent banking crisis. During this period the average size of the shadow economy in Cyprus based on the currency approach is estimated around 11-18% of GDP while for the electricity consumption the respective estimates are on average between 25%-34%.
Keywords: Black economy; Underground economy; Macroeconomic approach; Time-series methods